Substance abuse and its psychiatric effect on adolescence - Alghamdi, Badr; Zrari, Mohammed; Elahi, Alaa; Alwagdani, Meshari; Alghamdi, Eman; Moafa, Hashem; Miran, Shaher; Alamoudi, Shahad; Alshahrani, Khaled; Binnwejim, Mohammed; Jaafari, Marwan (International Journal Of Community Medicine And Public Health, 2018)
Substance abuse amongst adolescence is a widespread health issue that witnesses a progressive increase over years. Substance abuse among this age group is associated with significant psychiatric morbidities that differ according to the substance used. Many literature studies were conducted to explore the psychiatric conditions and consequences associated with substance abuse. To date, cannabis was the most common substance studied and the most well-known illicit drug to be associated with various psychiatric co-morbidities. Other studied substances include alcohol, opiates, barbiturates, hallucinogens, and inhalants. The psychiatric effects of various substances depend on the state, the duration, and the dose of their use. This article will review and discuss the short-term and long-term effects of these substances on the mental health among adolescence.